2008
DOI: 10.1002/prot.22135
|View full text |Cite
|
Sign up to set email alerts
|

Human FEZ1 has characteristics of a natively unfolded protein and dimerizes in solution

Abstract: The fasciculation and elongation protein Zeta 1 (FEZ1) is the mammalian orthologue of the Caenorhabditis elegans protein UNC-76, which is necessary for axon growth. Human FEZ1 interacts with Protein Kinase C (PKC) and several regulatory proteins involved in functions ranging from microtubule associated transport to transcriptional regulation. Theoretical prediction, circular dichroism, fluorescence spectroscopy, and limited proteolysis of recombinant FEZ1 suggest that it contains disordered regions, especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 65 publications
2
58
0
Order By: Relevance
“…46 Specific complex formation between IDPs is quite unusual, but not unprecedented. 47 Homodimerization of IDPs was first reported in 2004 for a novel class of signaling-related IDPs 9 and later confirmed for other IDPs [48][49][50][51] extending the phenomenon to different classes of IDPs and suggesting physiological relevance. It should be noted that in most of these studies, dimerization is accompanied by a mutual or "synergistic" 47 folding of two IDP molecules at the interaction interface (Fig.…”
Section: Protein Order Disorder and Oligomericity In Transmembramentioning
confidence: 85%
See 2 more Smart Citations
“…46 Specific complex formation between IDPs is quite unusual, but not unprecedented. 47 Homodimerization of IDPs was first reported in 2004 for a novel class of signaling-related IDPs 9 and later confirmed for other IDPs [48][49][50][51] extending the phenomenon to different classes of IDPs and suggesting physiological relevance. It should be noted that in most of these studies, dimerization is accompanied by a mutual or "synergistic" 47 folding of two IDP molecules at the interaction interface (Fig.…”
Section: Protein Order Disorder and Oligomericity In Transmembramentioning
confidence: 85%
“…IDPs are often referred to as "remaining predominantly disordered" or "largely unfolded" upon dimerization or interaction with other proteins or lipids, 35,[39][40][41][42][43][44][45][48][49][50][51] meaning that the protein regions flanking the interaction interface but not the interface itself remain disordered. Recently, it has been suggested to term this mode of interaction "the flanking fuzziness" in contrast to "the random fuzziness" when the IDP remains entirely disordered in the bound state.…”
Section: Intrinsically Disordered Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…This latter domain has been demonstrated to form homodimers without a disorder-order transition [48]. Interestingly enough, the T-cell receptor belongs to a group of receptors whose signaling depends on a two-step monomer-dimer-tetramer fast dynamic equilibrium [49]; this oligomerization of the intrinsically disordered region is essential to the receptor signaling [50,51]. We hypothesize that the C-TRPV1 self-associated species might be originated by suffering a very similar process, being the domain oligomerization the essential step for an effective signaling of the whole TRPV1.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, these studies not only challenge the generally accepted paradigms in protein functional role of IDP homointeractions in transmembrane signaling. 1,3,9,10 Later, in independent studies by several groups, other IDPs have also been found to form specific homodimers [11][12][13][14] and shown to function through dimer formation, 11,14 confirming a direct functional link between protein intrinsic disorder and oligomericity.…”
Section: Dimerization Of Intrinsically Disordered Proteinsmentioning
confidence: 99%